2018
DOI: 10.1371/journal.pone.0203487
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability as predictor of mortality in sepsis: A systematic review

Abstract: BackgroundAutonomic dysregulation is one of the recognized pathophysiological mechanisms in sepsis, generating the hypothesis that heart rate variability (HRV) can be used to predict mortality in sepsis.MethodsThis was a systematic review of studies evaluating HRV as a predictor of death in patients with sepsis. The search was performed by independent researchers in PubMed, LILACS and Cochrane, including papers in English, Portuguese or Spanish, indexed until August 20th, 2017 with at least 10 patients. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 41 publications
1
57
1
2
Order By: Relevance
“…Hypoalbuminemia and old age were well-known risk factors for poor outcomes and were published previously 15 . As to the association between HRV indices and infection-associated mortality, a systematic review disclosed that low values of several HRV indices, including variance, TP, VLF, LF, LF/HF ratio, and nLF could predict mortality in sepsis patients 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoalbuminemia and old age were well-known risk factors for poor outcomes and were published previously 15 . As to the association between HRV indices and infection-associated mortality, a systematic review disclosed that low values of several HRV indices, including variance, TP, VLF, LF, LF/HF ratio, and nLF could predict mortality in sepsis patients 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This effect of nHF on infection-associated mortality had not been summarized in the recent systemic review 34 . Although some studies suggested that vagal activities might be beneficial in sepsis 35,36 , other investigations reported that the HF was significantly higher in the nonsurvivors than in the survivors among septic patients 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low HRV is associated with mortality in various diseases [27][28][29][30] . In the present study, we found that all of the analyzed traditional HRV parameters, as well as conventional non-linear measures and CI, were significantly different between the ESRD and healthy control groups except for the Mean RR.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in HRV maybe associated with impending septic shock and increased mortality in sepsis patients (Chen and Kuo, 2007;de Castilho et al, 2018). A systemic review of clinical studies suggested a reduction in HRV parameters in non-surviving sepsis patients (de Castilho et al, 2018).…”
Section: Variability Characterizes the Biological Systems And Heart mentioning
confidence: 99%
“…Changes in HRV maybe associated with impending septic shock and increased mortality in sepsis patients (Chen and Kuo, 2007;de Castilho et al, 2018). A systemic review of clinical studies suggested a reduction in HRV parameters in non-surviving sepsis patients (de Castilho et al, 2018). In one study, after adjusting for SOFA and acute physiology and chronic health evaluation II (APACHE II) scores, an SDNN of ≤17 ms was associated with a hazard ratio of 6.3 for increased mortality (de Castilho et al, 2017).…”
Section: Variability Characterizes the Biological Systems And Heart mentioning
confidence: 99%